2021
DOI: 10.3389/fvets.2021.806653
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Escherichia coli From Aquaculture Farms and Their Environment in Zhanjiang, China

Abstract: Antimicrobial resistance (AMR) has become a major concern worldwide. To evaluate the AMR of Escherichia coli in aquaculture farms of Zhanjiang, China, a total of 90 samples from the water, soil, and sediment of three aquaculture farms (farms I, II, and III) in Zhanjiang were collected, and 90 strains of E. coli were isolated for drug resistance analysis and AMR gene detection. The results indicated that the isolated 90 strains of E. coli have high resistance rates to penicillin, amoxicillin, ampicillin, tetrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Their detections cannot exclusively represent an improper GHP application. Indeed, Staphylococcus spp., which have frequently harbored these tet and erm genes, are part of the normal microbiome identified from salted and seasoned codfish or other salted or fermented fish species [ 14 , 29 , 43 , 51 ]. Secondly, horizontal ARG transmission has a key role in their spreading among organic substrates [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their detections cannot exclusively represent an improper GHP application. Indeed, Staphylococcus spp., which have frequently harbored these tet and erm genes, are part of the normal microbiome identified from salted and seasoned codfish or other salted or fermented fish species [ 14 , 29 , 43 , 51 ]. Secondly, horizontal ARG transmission has a key role in their spreading among organic substrates [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 392/684, or 57.30%, (95% CI: 53.60–61.00%) bacterial strains harbored numerous ARGs ( bla TEM , bla CIT , bla CTX-M , bla KPC , bla IMP , bla OXA-48-like , tet C, tet K, tet L, erm B, erm C, sul 2, and sul 3) against specific antibiotic classes that were not phenotypically expressed (See Table 8 ). Indeed, the wide detection of ARGs is not always associated with their encoding and its consequential transcriptions [ 29 ]. The suggested scientific hypothesis was that these commensal or pathogenic strains were involved as microenvironmental reservoir forms of resistance, in agreement with previous studies [ 29 , 51 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEM gene was identified in fish body and gills. This gene has been found in pisciculture farms [26,27]. Most Aztreonam and Cephalosporin resistance could be attributed to TEM-lactamase, which has the potential to hydrolyze monobactam, first generation cephalosporins, and extended spectrum cephalosporins.…”
Section: Distribution Of Extended Spectrum Beta-lactamase Producing E...mentioning
confidence: 99%
“…Microorganisms are an important part of the aquatic environment, which play an important role in the response to antibiotics, the spread of drug resistance, and environmental remediation ( 19 ). It has been found that the antibiotics could directly affect the drug resistance of environmental microflora, thus causing environmental toxicity ( 20 , 21 ). However, the relevant reports about the impact of enrofloxacin on the microbial community in the aquatic environment are limited.…”
Section: Introductionmentioning
confidence: 99%